INTRAC's analytical skills programme in Central Asia 2002–2015: an analysis of its aims, methodology, and results. Issue 5 (4th July 2022) - Buxton, Charles; Giffen, Janice; Moldosheva, Anara
ABSTRACT: The article describes the genesis and application of a training programme for analytical and research skills for NGOs in the ex-soviet republics of Central Asia. This modular course was used in different programme contexts (civil society support, poverty reduction, conflict resolution) in a fast changing external environment. The article presents the aims, methodology, types of participants, and local research studies produced. It discusses the challenges in encouraging open-ended analysis while at the same time focusing on realistic action research studies, and how the programme supported a community of practice and small advocacy projects to lobby and disseminate results.